Hypospadias and halogenated organic pollutant levels in maternal mid-pregnancy serum samples - Carmichael, Suzan L (2010)
BACKGROUND: Environmental contaminants that disrupt endocrine function may contribute to hypospadias etiology. OBJECTIVE: To compare levels of selected halogenated organic pollutants in women delivering infants with and without hypospadias. METHODS: This study examined levels of nine polybrominated flame retardants (PBDEs), 30 polychlorinated biphenyls (PCBs) and nine persistent pesticides in mid-pregnancy serum samples from 20 women who delivered infants with hypospadias and 28 women who delivered unaffected infants, in California. Analytes were measured using isotope dilution high-resolution mass spectrometry. Values below individual limits of detection (LOD) for each analyte were imputed based on a truncated multivariate normal distribution. Levels of 17 analytes for which at least 50% of cases and controls had values above the LOD were compared using t-tests and by generating odds ratios from logistic regression analyses. RESULTS: Means were greater for cases than controls for 11 of the 17 reported analytes (4 of 5 PBDEs, 7 of 9 PCBs, and 0 of 3 other persistent pesticides), but none of the differences were statistically significant. Eleven of the 17 odds ratios exceeded one (the same analytes that had greater means), but none of the confidence intervals excluded one. After adjustment for sample processing time and foreign-born Hispanic race-ethnicity, only four of the odds ratios exceeded one. CONCLUSIONS: Levels of the PBDEs and PCBs were not statistically significantly different, but the sample size was small. The current study adds to a relatively limited knowledge base regarding the potential association of specific contaminants with hypospadias or other birth defects.